A STUDY OF THE IMPACT OF LAND USE AND OCCUPATION ON BASIN WATER QUALITY THROUGH MULTIVARIATE STATISTICS - Santos, Gilmar O.; Hernandez, Fernando B. T. [UNESP]; Ferraudo, Antonio S. [UNESP]; Vanzela, Luiz S.; Santos, Duilio J. O. (Soc Brasil Engenharia Agricola, 2017)
Without effective actions to improve environmental management, water resources tend to become scarce. Thus, this study aimed to understand the processes influencing the physical, chemical, and biological properties of the water due to land uses and occupation in the Ipe stream basin, in Ilha Solteira - SP (Brazil), regarding the dependence of the analyzed variables. Monitoring of chemical, physical, and biological water quality was performed from 2006 to 2011, and the records of land use and occupation in 2011. A factorial multivariate analysis allowed us to understand that the processes in densely populated areas increased degradation of water by the input of organic loads, yet those of farming areas enhanced the degradation of the chemical and physical quality of spring waters. Therefore, installing irrigation systems near populated areas, for crops consumed in natura, may compromise this agricultural activity, as well as the absence of water filtration systems downstream agricultural areas. Furthermore, we concluded that multivariate statistics is a powerful tool to detect these influencing processes in water quality. In this study, this type of analysis played an important role isolating the processes acting on water quality.
Keywords: factor analysis; irrigation; land use and occupation; river basin